Performance of rare earth oxide doped Mn-based sorbent on various silica supports for hot coal gas desulfurization. (1st August 2016) - Huang, Z.B.; Liu, B.S.; Tang, X.Y.; Wang, X.H.; Amin, R.
Graphical abstract: Highlights: Pore structure and thermal stability of support played important roles during desulfurization. Doping rare earth oxides promoted high dispersion of active particles. Induced effect of rare earth oxides are CeO2 > La2 O3 > Sm2 O3 . Steam in hot coal gas suppressed the desulfurization efficiency and precision. Mn/MCF sorbent was stable with complete regenerated ability. Abstract: A Mn-based sorbent with high desulfurization efficiency were fabricated using various mesoporous silica as support and doping rare earth oxides, and their physical properties were characterized by means of XRD, BET, H2 -TPR, CO2 -TPD, O2 -TPD and UV–Vis techniques. The results indicated that Mn/MCF exhibited the highest desulfurization performance among Mn/MCM-41, Mn/SBA-15, Mn/MCM-48 and Mn/MCF due to the 3-D ultra-large mesopores and excellent thermal stability of MCF at 700 °C. Doping rare earth oxides into Mn/MCF can make the high dispersion of active particles. But the breakthrough sulfur capacities (BSCs) over 95Mn5Ce/MCF, 95Mn5La/MCF and 95Mn5Sm/MCF sorbents are lower than Mn/MCF sorbent due to the lower BSCs of CeO2, Sm2 O3 and La2 O3 themselves and the lower S BET and VT . The desulfurization efficiency and precision further declined with increasing steam content for Mn/MCF sorbent. The high sulfur capacity over the Mn/MCF sorbent was maintained during the five consecutive desulfurization/regeneration cycles.